missing Jesus: Rabbinic Judaism and the New Testament - Chilton, Bruce (Brill Academic Publishers, 2002)
How can Jesus said to be "missing"? References to Jesus are not missing, but rather a dimension of his identity. This text demonstrates that in order for us to understand Jesus and his influence, we need to see him within the context of the Judaism that was his own natural environment.